The threshold displacement energy of buckminsterfullerene C60 and formation of the endohedral defect fullerene He@C59. (November 2018) - Stockett, Mark H.; Wolf, Michael; Gatchell, Michael; Schmidt, Henning T.; Zettergren, Henning; Cederquist, Henrik
Abstract: We have measured the threshold center-of-mass kinetic energy for knocking out a single carbon atom from C 60 − in collisions with He. Combining this experimental result with classical molecular dynamics simulations, we determine a semi-empirical value of 24.1 ± 0.5 eV for the threshold displacement energy, the energy needed to remove a single carbon atom from the C60 cage. We report the first observation of an endohedral complex with an odd number of carbon atoms, He@C 59 −, and discuss its formation and decay mechanisms. Graphical abstract: Image 1